De novo genome assembly of Wickerhamomyces ciferrii - 이지현 (The Graduate School, Ajou University, 2024)
The yeast strain Wickerhamomyces ciferrii, recognized for its proficiency in sphingolipid production, particularly tetraacetylphytosphingosine (TAPS), holds the potential for converting TAPS into ceramide, a process relevant to human skin sphingolipids with pharmaceutical applications. W. ciferrii's capability in TAPS production positions it as an ideal platform strain. Despite its potential, challenges exist due to the incomplete genome sequencing of W. ciferrii, including imperfect contigs and a lack of information about chromosome size and number. To address these challenges, we conducted a whole-genome assembly of W. ciferrii using Linux-based open-source tools. Hybrid sequencing, assembly, polishing, and annotation of the diploid two strain of W. ciferrii genome, were performed using tools such as Canu for assembly, Pilon for polishing, and Funannotate for annotation. Our efforts yielded high-resolution complete genome-level genome sequences of two strains of W. ciferrii (wild type and mutant 736) and one mitochondrial genome sequence in this diploid organism, respectively. The whole genome sequence, comprising contigs, is gap-free and exhibits higher gene completeness (wild type: 98.2 %, 736: 98.3 %) compared to the previously published reference sequence (97.8 %) with 13,897 and 13,519 annotated genes, respectively. While computational methods have inherent limitations, our study provides previously unavailable information about W. ciferrii's whole genome sequence. This research is significant as it lays the foundation for strain improvement and the use of W. ciferrii as a platform strain, offering new avenues for research and applications.|희귀한 지질 계열인 스핑고리피드, 특히 테트라아세틸피토스핑고신(TAPS)의 과생산과 높은 분비능으로 알려진 효모 균주 위커하모마이세스 시페리는 TAPS를 세라마이드로 전환시킬 수 있는 잠재력을 가지고 있다. 현재는 생산된 TAPS를 간단한 화학적 공정을 통해 세라마이드로 변환하여 사용하는데 이 물질은 화장품 산업, 의약 산업에서 많은 수요가 있는 물질이다. 따라서 TAPS 생산에 따른 위커하모마이세스 시페리의 능력을 활용하여 산업적으로 이상적인 플랫폼 균주로 사용하기에 충분한 가능성이 있는 균주로 판단할 수 있다. 하지만 이러한 잠재력에도 불구하고 위커하모마이세스 시페리는 불완전한 유전체 서열 및 염색체 개수에 대한 정보 부족을 포함하여 짧은 유전체 시퀀싱으로 인해 유전체의 해상도가 낮다는 한계점이 존재한다. 문제를 해결하기 위해 Linux 기반 오픈 소스 도구를 사용하여 위커하모마이세스 시페리의 전체 유전체 제작을 진행했다. 야생형 이배체 위커하모마이세스 시페리 유전체의 하이브리드 시퀀싱, 어셈블리, 폴리싱 및 주석 단계로 진행된 연구는 어셈블리용 Canu, 폴리싱용 Pilon 및 주석용 Funannotate와 같은 도구를 사용하여 수행되었다. 이 연구를 통해 이배체 유기체에서 위커하모마이세스 시페리의 두 가지 균주(야생형 및 돌연변이 736)의 유전체 지도와 한 가지 미토콘드리아 유전체 서열의 고해상도이며 유전체 수준 서열을 제작했다. 유전체를 구성하는 전체 콘티그의 서열은 갭이 없으며 각각 13,897 개 및 13,519 개의 예측 단백질 발현 유전자를 가지고, 이전에 발표된 서열(97.8 %)에 비해 더 높은 유전자 완성도(야생형: 98.2 %, 736: 98.3 %)를 나타내었다. 컴퓨터 분석을 통해 진행한 연구에는 한계점이 있지만, 이 연구로 기존에 알려진 유전체 서열보다 더 해상도 높은 유전체 수준의 서열을 제작하였다. 균주 개량 및 위커하모마이세스 시페리를 플랫폼 균주로 사용할 수 있도록 연구 및 응용을 위한 새로운 방법을 제공한다는 점에서 의의가 있다.
학위논문(석사)--분자과학기술학과,2024. 2
Keywords: Wickerhamomyces ciferrii; genome assembly; whole genome; yeast